Bank Selection and Patronage By University Students: A Survey of Students in Umudike, Nigeria - Okpara, Gazie S.; Onuoha, Onuoha A. (Asian Business Review, 2013)
University students represent an attractive segment of customers for retail banks  in many countries including Nigeria. The objective of this study is to find out the determinants of the choice of commercial banks by university students, using Michael Okpara University of Agriculture, Umudike (MOUAU). MOUAU is selected due to the plurality of its student mix, being the only federal university in Abia State. Data were collected through self-administered questionnaire to 250 final year students, across the university’s ten colleges. Convenience sampling was used. Apart from the traditional analytical tools such as tables and percentages, data were also analysed using descriptive statistics and principal component analysis. The Cronbach’s alpha was used to test the reliability of the measuring instrument. The results show that service is the most influential of all the six determinant-factors for the choice of commercial banks. Proximity, attractiveness, referrals, marketing and price followed suit, based on their mean scores.  Recommendations were proffered for competitive bank management, focused on different market segments among university students.